Aspergillus flavus (Link) toxins reduces the fitness of dengue vector Aedes aegypti (Linn.) and their non-target toxicity against aquatic predator. (March 2019) - Vasantha-Srinivasan, Prabhakaran; Karthi, Sengodan; Chellappandian, Muthiah; Ponsankar, Athirstam; Thanigaivel, Annamalai; Senthil-Nathan, Sengottayan; Chandramohan, Devarajan; Ganesan, Raja
Abstract: Mosquito that accountable for dispersal of dengue fever is Aedes aegypti Linn. and considered to be a chief vector for dengue especially in South Asian countries. Aspergillus flavus is considered to be wild growing green yellow colonies and synthesis highly regulating aflatoxins (B1, B2, G1 and G2) as a secondary metabolite. Mycotoxins of A. flavus showed its efficacy against III and IV instars of Ae. aegypti with more than 90% mortality at the prominent dosage of 2 × 10 8 conidia/ml. The proximate lethal concentrations (LC50 and LC90 ) of mycotoxins against third and fourth instars was 2 × 10 5 and 2 × 10 7 respectively. Correspondingly, sub-lethal dosage of mycotoxin A. flavus significantly inhibited the level of α- β-carboxylesterase and SOD activity and upregulated the level of major detoxifying enzymes GST and CYP450. Moreover, sub-lethal dosage also showed higher deterrent and fecundity effects. Gut-histological examination reveals that the A. flavus considerably affected the gut epithelial cells along with the inner gut lumen as compared to the control. The non-target screening of A. flavus against two aquatic predators ( A. bouvieri and Tx. splendens ) display more than 80% of mortality rate against both the species at the dosage of 2 × 10 16 (two-fold-higher dosage used in larval assays). Thus the biosafety assessment suggests that A. flavus display higher toxicity against the non-targets and it is not-recommended to apply it directly to the aquatic habitat of dengue mosquito which shares their living space with other beneficial insects. Highlights: Aspergillus flavus fungus against the toxicity of dengue vector and non-target organisms of aquatic predator. Mycotoxins showed toxicity against III and IV instars of Ae. aegypti with more than 90% mortality at 2 × 10 8 conidia/ml. α- β-carboxylesterase and SOD activity was up-regulated the level of major detoxifying enzymes GST and CYP450. The gut epithelial cells considerably affected along with the inner gut lumen of mosquito vectors.